Ecosystem-Based Adaptation and Indigenous Solutions for Climate Change in Kenya and Africa - Dinah Awino; Nancy Nyambura (My University, 2025)
This blog series explores the critical role of Ecosystem-Based Adaptation (EbA) and Indigenous Knowledge Systems in addressing climate change across Kenya and Africa. Through four insightful blogs, we delve into EbA principles, highlight the deep-rooted wisdom of Indigenous communities in shaping sustainable adaptation strategies, and examine the synergy between EbA and biodiversity conservation. The series also showcases community-led initiatives, emphasizing the power of local engagement in fostering climate resilience. By weaving together scientific approaches and traditional ecological knowledge, this series aims to inform, inspire, and advocate for nature-based solutions tailored to Africa’s unique environmental and socio-cultural landscape.
Kukabiliana na Mfumo-ikolojia na Suluhu za Wenyeji kwa Mabadiliko ya Tabianchi nchini Kenya na Afrika
How can nature help us adapt to climate change? This blog dives into Ecosystem-Based Adaptation (EbA), showcasing real-world examples of how communities in Kenya and Africa are using indigenous knowledge and natural solutions to build resilience while protecting biodiversity.
Keywords: Biodiversity Conservation; Ecosystem-based Adaptation; Sustainability; Climate Change; Indigenous Knowledge Systems; Community; Resilience; Adaptation strategies